(untitled) (Acta Judicial Journal, 2024)
Judicial public faith, a cornerstone of the Spanish Procedural Law system, stands as a fundamental principle in the context of emerging technologies. It´s significance lies in the system’s ability to effectively verify legal representation within the judicial sphere. This not only ensures the authenticity and integrity of judicial acts and documents but also fosters the trust of all parties involved in the procedural system. Furthermore, this digital approach carries broad implications for the modernization of the legal system in Spain. The successful implementation of electronic empowerments not only streamlines judicial procedures but also aligns the judicial system with global technology and digitization trends, bringing significant benefits to the administration of justice and the protection of citizens’ rights. With this work, the aim is to analyze the normative and practical impact of electronic empowerments in connection with the judicial public trust towards the ultimate frontier of technology.